Obsessive encounters - Storch, Anne; Traber, Janine (AAeO - Afrikanistik-Aegyptologie-Online, 2021)
This article is about travel as transgression, pilgrimage and fetish. It bases on empirical research conducted by the authors at now-closed sites of transgressive party tourism in El Arenal on the island of Mallorca. Constructions of transgression and lostness are seen as being complex: Getting lost while traveling is regarded as part of the scripted confusion in the tourist zone. We therefore investigate the noise in the beer halls as opportunities for the tourists to create meaning in situations when one does not know how to articulate oneself properly. Instead of leading to destruction, the lack of ordered language, we argue, serves the reification of order. Through the production of ambiguity and meaning, community could be created. Despite the abrupt halt of the tourism industry due to the pandemic in 2020, this need for ritual transgression and community making did not disappear. By its unavailability, the outcry for the rituals became even more channeled on digital platforms. Soon, products were sold online that should help to replace those which could usually be found in the shops in El Arenal. Implementing the consumerist part of the imaginary of adventure, the items further deliver the previously performed mockery of the marginalized to the holiday makers in their home apartments. The ritual transgression by tourists at the Spanish party site always involved giving a role to West African migrants. As ambulant vendors, by wearing carnivalesque costumes and selling items such as sunglasses, they were to offer moorings for order to be restored, making racism and segregation along the boundaries constructed by classism obvious parts of the consumption and excess in the area. The street vendors, who could before at least slightly benefit in a financial way from their inclusion in the party industry at the beach, were then completely bypassed by the online T-shirt sales, and the hostility of the images representing them increased. We argue that, with reference to Walter Benjamin, these transgressive objects at the cost of marginalized and precarious Others were necessary for the upholding of ritual confusion and the following reinstallation of order.